Remote water sampling using flying robots. - Schwarzbach, Marc; Laiacker, Maximilian; Mulero-Pázmány, Margarita Cristina; Kondak, Konstantin (My University, 2014)
Sampling of water for laboratory measurements is important in various circumstances. We present reasoning why it is of great importance for sensible ecosystems like natural parks wich include wetlands. Since many places are hard or impossible to reach by other means, a system for sampling of water using an unmanned helicopter is proposed. The technical difficulties in handling the sample and controlling the system are described as well as apropriate solutions. The system was also integrated into a control framework allowing easy access and control by scientists, in our case biologists. Several trials have been performed, including flights in the final application fields. Water samples could be acquired reliably.
Keywords: Biodiversidad - Conservación - Innovaciones tecnológicas; Aviones sin pìloto; Drones; Biodiversity